Pituitary Adenoma Presenting As Trigeminal Neuralgia - Abrar A. Wani; Altaf U. Ramzan; Abdul Q. Khan; Nayil K. Malik; Khalid Pervez (Indian Journal of Neurosurgery)
Compression of trigeminal nerve in cavernous sinus leading to trigeminal neuralgia is one of the rare presentations of pituitary tumor. We report a patient whose presenting complaint was trigeminal neuralgia in V1, V2 distribution and he had pituitary macroadenoma invading ipsilateral cavernous sinus. After surgery, the neuralgia disappeared completely.